Leptospirosis: New Emerging Disease in Sukoharjo District (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
Leptospirosis in Sukoharjo was discovered in 2014. Examination with RDT (Rapid Diagnostic Test) leptotek supported by clinical symptoms showed 6 positive cases of Leptospira, and until March 2015 one person was found to be Leptospira positive. The aim of this study was to identify rats as the main reservoir of leptospirosis, calculate the catching rate of rats and to detect the presence of pathogenic Leptospira in rats. This study was a cross-sectional survey, and was conducted in Pabelan village Kartasura Sukoharjo on May 2015. Polymerase Chain Reaction (PCR) assay was conducted in Bacteriology Laboratory Balai Litbang P2B2 Banjarnegara to detect leptospira in the kidney of the rats. Data were analyzed descriptively. Results of rats and shrew catching obtained Rattus tanezumi, Rattus norvegicus and Suncus murinus. The species most commonly found was balanced between R. tanezumi and S.murinus (46%). The trap success rate inside and outside the house are 1.50% and 5%, respectively. Result of laboratory test showed from 13 rats kidneys, two kidneys were found to be Leptospira positive and was from R.tanezumi and R.norvegicus.